(untitled) (Nepal Journal of Epidemiology, 2016)
Strict law enforcement is required to ensure compliance with safety measures and necessary precautions to avoid health risks at the workplace. There is also a need for multi-agency review of health provision for migrant workers, which should be based on thorough and independent evaluation for the major causes of mortality among migrant construction workers, and identifying key measures to improve health and safety of workers.